Governance Capacity and STCW Compliance in Maritime Education: A PCA–FASTCLUS Approach - Antonius Edy Kristiyono; Ariyono Setiawan; Iie suwondo; Warju Warju; Deshinta Arrova Dewi (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Maritime accidents remain influenced by human and institutional factors despite strengthened global regulations. However, variations in Standards of Training, Certification, and Watchkeeping for Seafarers (STCW) compliance across maritime education institutions indicate that compliance alone does not fully explain safety readiness. This study examines how governance capacity shapes STCW compliance as an intermediate institutional capability. Using survey data from 109 maritime education institutions in Indonesia, this study applies Principal Component Analysis (PCA), multiple regression, ΔR² analysis, and FASTCLUS clustering to capture structural priorities and institutional heterogeneity. The results show that resource availability (β ≈ 0.31) and implementer disposition (β ≈ 0.27) are the most influential factors, jointly accounting for over 59% of the explained variance. Despite similar compliance levels, institutions exhibit different governance configurations, indicating latent heterogeneity. These findings suggest that compliance should be interpreted as a capacity-driven process rather than a procedural endpoint. The study contributes by integrating multivariate and configurational approaches to reframe compliance as an institutional capability mechanism and provides policy implications for shifting from compliance enforcement to capacity development in maritime education systems.